Children's graves at the Middle La Tène cemetery of Zvonimirovo (Croatia) - Marko Dizdar (Arheološki Vestnik, 2025)
The cemetery of Zvonimirovo is currently the only systematically researched cemetery of the La Tène culture in northern Croatia that can be dated to the Middle La Tène period (LT C2). Previous research studies were focused on richly equipped graves of warriors with weapons and of women with costume and jewellery items. The results of the anthropological analysis indicate that children under 14 years of age were also buried at the cemetery and received the same mortuary treatment as the adult members of the community. Children were most often buried alone, as the only deceased in the grave, but a smaller number of graves contains a child with an adult. The study of mortuary profiles of children’s graves indicates that the majority of them contained fewer finds than the graves of adults, but some of them were richly equipped. Aside from pottery, children’s graves contained costume and jewellery items, with weaponry appearing exceptionally. Similar mortuary profiles of children’s graves have been documented in the analyses of La Tène cemeteries in the Carpathian Basin, indicating their position in the Late Iron Age communities.